Diagnosing the barriers for integrating Educational Technology in Physics courses in Lebanese secondary schools - Fouad Yehya Yehya; Aziz Barbar; Suzanne Abou Rjeily (Research in Social Sciences and Technology- OpenED Network, 2018)
This paper investigates the barriers affecting the success implementation of ICT in the Lebanese secondary physics classes. It is realistic based study adopted the descriptive quantitative method to collect data by attitude test survey from 94 Lebanese secondary schools from different Lebanese districts. The results indicated that the ICT implementation in physics courses was not attained. Physics teachers must improve their ICT skills. Moreover, the low technology periods per week and revealing curriculum content, inflexibility of the curriculum to ICT implementation, insufficient existence of computer labs, lack financial support, insufficient training, inadequate technical support, unavailability of internet connectivity and the crowded class rooms were main barriers that prevent the implementation of ICT.